Peran Inovasi Produk Sebagai Strategi Meningkatkan Daya Saing Usaha Sushi Somoji - Ani Apriyani; Ike Roslita; Firda Hayati (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2026)
The culinary industry in Indonesia has become increasingly competitive due to lifestyle changes and the growing number of Micro, Small, and Medium Enterprises (MSMEs). This situation requires business actors to implement appropriate strategies to enhance competitiveness and ensure business sustainability. One such strategy is product innovation. This study aims to analyze the role of product innovation as a strategy to improve the competitiveness of Sushi Somoji. This research employed a qualitative approach using a case study method. The research subject was Sushi Somoji, an MSME engaged in the sushi culinary business. Data were collected through direct observation, interviews with the owner and employees, and documentation. The data were analyzed using descriptive qualitative analysis through data reduction, data presentation, and conclusion drawing. The findings reveal that product innovation at Sushi Somoji focuses on developing various sushi toppings as a form of product differentiation. This innovation increases visual appeal, accommodates consumer preferences across different age groups, and creates product uniqueness compared to similar businesses. Moreover, topping-based innovation is considered effective because it can be implemented at a relatively low cost without altering the basic taste of sushi. In conclusion, product innovation plays an important role in enhancing the competitiveness of Sushi Somoji and supporting business sustainability amid intense competition in the culinary industry.